2021
DOI: 10.1021/acscatal.1c00185
|View full text |Cite
|
Sign up to set email alerts
|

C(sp3)–H Selective Benzylic Borylation by In Situ Reduced Ultrasmall Ni Species on CeO2

Abstract: Herein, we report that highly dispersed Ni hydroxide species supported on CeO2 act as an efficient heterogeneous catalyst for the selective borylation of benzylic C­(sp3)–H bonds of alkylarenes including secondary derivatives, using pinacolborane as the borylating agent. A thorough physicochemical analysis reveals that in situ reduced ultrasmall Ni species on CeO2 during the reaction are the actual active species responsible for the borylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…However, unexpectedly with 3 b also a significant amount of hydrogen‐deuterium exchange was observed in the propyl chain. Aromatic and benzylic H/D exchange with Ni 0 and HBpin are reported in literature [21, 22] . Benzylic C(sp 3 )−H activation followed by β‐hydride elimination and reinsertion of Ni−H explain the observed methylene deuteration further in the propyl chain.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, unexpectedly with 3 b also a significant amount of hydrogen‐deuterium exchange was observed in the propyl chain. Aromatic and benzylic H/D exchange with Ni 0 and HBpin are reported in literature [21, 22] . Benzylic C(sp 3 )−H activation followed by β‐hydride elimination and reinsertion of Ni−H explain the observed methylene deuteration further in the propyl chain.…”
Section: Resultsmentioning
confidence: 76%
“…Aromatic and benzylic H/D exchange with Ni 0 and HBpin are reported in literature. [21,22] Benzylic C(sp 3 )À H activation followed by β-hydride elimination and reinsertion of NiÀ H explain the observed methylene deuteration further in the propyl chain. These competitive reactions in the alkyl chain offer an explanation for the lower conversion of 3 b compared to conversion of 3 s. Similar results were obtained for 4-propylguaiacyl acetate (3 a) when using DBpin (see Supporting Information section 7).…”
Section: Resultsmentioning
confidence: 94%
“…developed a novel protocol for Pd(0)−catalyzed oxidative carbonylation of non‐directed benzylic C(sp 3 )−H bond [5] . Although significant progress has been made on chelation‐induced benzylic C(sp 3 )−H bond functionalization, [6] non‐directed benzylic C(sp 3 )−H bond functionalization is still less explored and a few of them were pioneered by Hiyama, [7a] Li, [7b] Landais, [7c] Chen, [7d] Chirik, [7e] Lei, [7f] Pandey, [7g] Xing, [7h] White, [7i] Takemoto, [7j] Qing, [7k] Shi, [7l] Wu, [7m] Bolm [7n] and Yamaguchi [7o] for Heck‐type couplings with diverse electrophiles (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…These surface effects become more important for low Ni loadings. Recent studies have investigated Ni loadings equal to [44] and less [45] than 3 % supported on CeO 2 for other classes of reactions, and have observed that under oxidizing conditions, the Ni species were very reactive but deactivated quickly due to oxidation.…”
Section: Introductionmentioning
confidence: 99%